Implementation of Weighted Product Method to Determine Exemplary Students at SMKN 1 Purwakarta - Gito, Mochzen; Agus Sunandarag, Muhamad; Mochammad Imam Sulistyo Sarjow, Mochammad; Andayani Komara, Mutiara; Sukma H, Deden (RISTEC : Research in Information Systems and Technology, 2024)
The Weighted Product method is a method that can help in making decisions. The largest value will be selected as the best alternative. Calculations will be in accordance with this method if the selected alternative meets the specified criteria. SMKN 1 Purwakarta is one of the schools where in its academic activities there is a selection of exemplary students. The need for an easier and more objective election system is something worth considering. To meet these needs, research was conducted that implemented the Weighted Product method to select exemplary students based on academic, non-academic, organizational and extracurricular values. Based on the calculations, the highest preference value or V vector was 0.212. The data with the largest vector V value is then recommended to become an exemplary student